Innovation in Cavendish Banana Chips Processing: Business Opportunities and Digital Marketing - Fadilatun Naimah; Nur Maghfirotus Sa'adah; Aisah Ananda Ardyansah; Nabilah Ayu Jesica (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In Sumberanyar Village, Nguling District, Pasuruan Regency, there is a significant potential for Cavendish bananas that has not been fully optimized. This study aims to analyze the potential and challenges in the cultivation and processing of Cavendish bananas into banana chips in Sumberanyar Village, and to identify innovations that can be implemented to increase the value-added of this product. Additionally, this research aims to examine the role of the Asset-Based Community Development (ABCD) approach in empowering the village community. The methodology used in this research is the ABCD approach, which focuses on identifying and utilizing local assets for community economic development. This study involved banana processing workshops and digital marketing strategy development. Data was collected through interviews, observations, and surveys, and then analyzed to develop a comprehensive strategy for increasing product value-added and digital marketing. The research results indicate that innovation in processing Cavendish bananas into banana chips, supported by effective digital marketing, has the potential to improve the economic welfare of the village community. The conclusion of this study is that the application of the ABCD approach is effective in empowering the village community through product innovation and digital marketing, ultimately increasing the income and welfare of local people. Recommendations for further development include advanced training, product diversification, and optimization of digital marketing.